Pengalaman Hidup Pada Remaja Dengan HIV/AIDS Di Kota Bandung - Dewi Srinatania; Revy Citra Karlina (Risenologi, 2021)
Adolescence is closely related to psychological development in the pubertal period and is accompanied by sexual development. Adolescence is an age that is experiencing increased vulnerability to various health risk threats, especially those related to sexual and reproductive health, including the increased threat from HIV/AIDS. HIV/AIDS is one of the biggest problems for health workers and other care providers. People with HIV/AIDS do not only experience physical suffering due to the disease process, but also psychosocial suffering. People with HIV/AIDS (PLWHA) are often faced with complicated conditions to reveal or hide their disease condition. The purpose of this study is to describe the Life Experience of Adolescents with HIV/AIDS. This study uses the Qualitative Colaizzi analysis method with structured formal interviews with four adolescent participants diagnosed with HIV/AIDS who live in Bandung. Interviews were recorded and then made in the form of interview transcripts. There are 8 themes, namely: 1) Ignorance of the process, 2) Physical Symptoms, 3) Disease process, 4) Psychological impact, 5) Environmental response, 6) Economic impact, 7) Social support, 8) Participants' expectations. The results of the study reveal a variety of adolescent life experiences ranging from what they think, feel and experience after being diagnosed with HIV. The social support received by PLWHA is obtained from the family environment such as spouse, parents, friends, neighbors, group support, and health workers who are provided in the form of information support, social integrity, emotional, health services.